Development of Digital Learning Media Based on Wingeom Software on Geometry Material at PGRI 3 Tempurejo Junior High School - Sujiwo, Dimas Anditha Cahyo; Marsidi, Marsidi; Solehan, Muhamad (International Journal of Trends in Mathematics Education Research, 2025)
Digital learning media is one of the urgent factors in improving the quality of learning. It is said so because of the development of digital technology in the field of education that demands effectiveness and efficiency in learning and teaching. Development of learning media so that in the implementation of future learning is expected to be able to support the material delivered. This study aims to recognize media development in learning and test the feasibility of the WinGeom software learning media. Implementing the research and development (RD) research method of the ADDIE research model (analysis, design, development, implementation, and evaluation). The results obtained from this study are based on the assessment of the validator; namely, the material expert validator obtained a score of 45 out of 50 maximum scores with a percentage of 90% in the very feasible category. Media validation obtained a score of 40 out of a maximum score of 50 with a percentage of 80% and can be said to be feasible. Practitioner experts, namely those obtaining a score of 46 with a percentage of 92%, are in the very feasible category. As for student responses to the media that has been developed. The data results obtained with a percentage of 91% are categorized as very feasible for use in learning. In terms of student satisfaction in using Wingeom media, it shows that the majority of students (more than 60%) feel "very satisfied" with the use of Wingeom software in geometry learning. Furthermore, in terms of student learning outcomes before and after using Wingeom software, it shows an increase. These results are obtained from the average value of the pre-test, which is 59.7, and the average value of the post-test, which is 89.3. In the calculation of N-Gain, the N-Gain value is 0.73. These results indicate that Wingeom Software is very effective in improving students' conceptual understanding of flat geometry material.